2014
DOI: 10.17334/jps.30658
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fenugreek Herbal Tea and Palm Dates on Breast Milk Production and Infant Weight.

Abstract: IntroductionKnowledge of the biology of human milk and the physiology of its production, secretion, and delivery is critical in deeply understanding the benefits of breastfeeding. Human breast milk is the optimal nutrition for infants because of its proven advantages for both the infant, and the mother. The World Health Organization (WHO), the American Academy of Pediatrics (AAP), and the American College of Obstetricians and Gynecologists (ACOG) all recommend breastfeeding for the first six months of age [1].… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 11 publications
1
28
0
10
Order By: Relevance
“…After final scrutiny, only five randomized control trials were found eligible (Figure ). The results reported in these studies were collected from the participating women from Egypt (El Sakka, Salama, & Salama, ), Iran (Ghasemi, Kheirkhah, & Vahedi, ), USA (Reeder, Legrand, & O'connor‐Von, ), Turkey (Turkyilmaz et al, ), and Indonesia (Damanik, Wahlqvist, & Wattanapenpaiboon, ; Table ). For assessing the effect of fenugreek on lactation, various types of interventions were included in studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After final scrutiny, only five randomized control trials were found eligible (Figure ). The results reported in these studies were collected from the participating women from Egypt (El Sakka, Salama, & Salama, ), Iran (Ghasemi, Kheirkhah, & Vahedi, ), USA (Reeder, Legrand, & O'connor‐Von, ), Turkey (Turkyilmaz et al, ), and Indonesia (Damanik, Wahlqvist, & Wattanapenpaiboon, ; Table ). For assessing the effect of fenugreek on lactation, various types of interventions were included in studies.…”
Section: Resultsmentioning
confidence: 99%
“…Damanik et al () conducted a parallel‐randomized intervention study assessing the comparative effect of fenugreek seeds filled in hard capsules [one capsule three times daily] versus CA leaves as a comparator and the reference group receiving sugar‐coated Moloco + b12 ™ tablets for the duration of 2 months (60 days) with the mean gestational age for all groups ranging from 37 to 43 weeks (Damanik et al, ). El Sakka et al () investigated the effect of fenugreek herbal tea [one cup three times daily (2 table spoons, 2 g of fenugreek)] and using date palm as a comparator versus the reference group (no galactagogue). The study design was a randomized controlled trial, and the duration of this study was 244 days with the mean gestation age ranging from 37.6 to 39.2 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…However, few efficacy studies have been conducted. A randomized clinical trial of 75 lactating women in Egypt found that palm dates (Phoenix dactylifera) and fenugreek (Trigonella foenum-graecum) herbal tea enhanced breast milk production (Sakka et al 2014). Gbadamosi and Okolosi (2013) analyzed ten botanical galactagogues for their chemical constituents and antimicrobial activities finding that they had high protein, fiber, iron and calcium content, and antibacterial activity.…”
Section: Maternal Knowledge and Use Of Galactagogues In Andean Communmentioning
confidence: 99%
“…Among dates, fenugreek and control groups, only infant weights in date's group showed an increasing trend on the seventh day and there wasn't any remarkable difference among them on the fourteenth day. It was concluded that in early postpartum period, palm dates and fenugreek herbal tea seems to be applicable for enhancing breast milk production (63). In a study carried out in Turkey, the effect of herbal tea containing fenugreek on breast milk production and weight gain recovery of infants within the first postpartum week was evaluated.…”
Section: Application As a Galactagoguesmentioning
confidence: 99%